Performance standards for the GII. - Seitz, N.B.
This article summarizes the traditional process for developing international telecommunication performance standards and describes enhancements that will be needed to adapt the process for use in the emerging global information infrastructure (GII). The necessary enhancements are being developed under the auspices of ITU-T Study Group 13
Keywords: ATM; GII; ITU-T Study Group 13.; Global information infrastructure; International telecommunication performance standards; Networking technologies; Telecommunication services